GAMBARAN POLA MAKAN DAN PREVALENSI STUNTING PADA BALITA UMUR 12 – 59 BULAN - Misrawatie Goi; Fenli Charles Daed; Heni Panai (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2020)
ABSTRACT The eating pattern that is formed is closely related to a person's eating habits and will affect the nutritional status of toddlers such as stunting. This study aims to describe the diet and prevalence of stunting in toddlers aged 12-59 months in Tabumela village, Tilango sub-district, Gorontalo district. The research method uses a descriptive survey, namely a survey conducted to describe the variables studied. The population is 187 toddlers and the sample is 65 toddlers. Research variables include eating patterns and the incidence of stunting in toddlers. The results showed that from 65 samples of eating patterns under five in the good category, there were 40 people (61.5%) and 25 people in the poor category (38.5%). The prevalence of children under five who experienced stunting was 39 people (60.0%) and 26 people were not stunted (40.0%). The conclusion of the study showed that most of the eating patterns of toddlers were in good category and the prevalence of stunting with short and very short nutritional status. ABSTRAK Pola makan yang tebentuk sangat erat kaitannya dengan kebiasaan makan seseorang dan akan berpengaruh terhadap status gizi pada balita seperti stunting. Penelitian ini bertujuan unntuk mengetahui gambaran pola makan dan prevalensi stunting pada balita umur 12-59 bulan di desa Tabumela kecamatan Tilango kabupaten Gorontalo. Metode penelitian menggunakan survey deskritif yaitu survey yang dilakukan untuk menggambarkan variabel yang diteliti. Populasi sebanyak 187 Balita dan sampel 65 Balita. Variabel penelitian meliputi pola makan dan kejadian stunting pada balita. Hasil penelitian menunjukkan dari 65 sampel pola makan balita yang kategori baik berjumlah 40 orang (61,5%) dan kategori kurang berjumlah 25 orang (38,5%). Prevalensi anak balita yang mengalami stunting berjumlah 39 orang (60,0%) dan tidak stunting berjumlah 26 orang (40,0%). Kesimpulan penelitian menunjukkan sebagian besar pola makan balita dengan kategori baik dan prevalensi stunting dengan status gizi pendek dan sangat pendek.